2021
DOI: 10.1111/rda.13919
|View full text |Cite
|
Sign up to set email alerts
|

Development of sustainable performance index based on production, reproduction, health and longevity for genetic improvement of Sahiwal cattle

Abstract: An attempt was made for the first time in India to develop the performance indices for quantifying the relative emphasis to be given to production, reproduction, health and longevity traits for selection and genetic improvement of Sahiwal cattle in a sustainable manner. The study was conducted using information related to various production, reproduction, health and longevity traits spread over a period of 29 years in Sahiwal cattle. Using income and expenditure method, the relative economic values for 305 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Posterior mean of permanent environmental (above diagonal) and residual correlations (below diagonal) along with posterior standard deviation for different performance traits in Sahiwal cattle LMY, LL, PY, DPY, DP GP, CFI, DO and CI as 1935.13 kg, 2022.49 kg, 277.90 days, 12.62 kg, 43.90 days, 137.13 days, 286.82 days, 85.62 days, 134.22 days and 425.42 days, respectively in Sahiwal cattle.Means observed for different traits were in concordance with the results of earlier studies(Ratwan et al 2018a(Ratwan et al , 2019a(Ratwan et al , 2020b(Ratwan et al , 2021. Period of calving had signi cant (p < 0.01) in uence on all considered traits except DPY and GP.…”
supporting
confidence: 90%
“…Posterior mean of permanent environmental (above diagonal) and residual correlations (below diagonal) along with posterior standard deviation for different performance traits in Sahiwal cattle LMY, LL, PY, DPY, DP GP, CFI, DO and CI as 1935.13 kg, 2022.49 kg, 277.90 days, 12.62 kg, 43.90 days, 137.13 days, 286.82 days, 85.62 days, 134.22 days and 425.42 days, respectively in Sahiwal cattle.Means observed for different traits were in concordance with the results of earlier studies(Ratwan et al 2018a(Ratwan et al , 2019a(Ratwan et al , 2020b(Ratwan et al , 2021. Period of calving had signi cant (p < 0.01) in uence on all considered traits except DPY and GP.…”
supporting
confidence: 90%
“…Wolf et al (2011) reported that formulation of profit function from which economic values are derived depends on the traits considered in breeding objective. Economic values are important for judging the economic significance of traits to be incorporated in a breeding objective and economic value refers to the probable increase in herd annual profit due to a unit increase in the trait as a result of selection (Jorge-Junior et al 2007, Ratwan et al 2021a. Selection index generally refers to a linear combination of various traits which are used to calculate total score for each individual and is used as a selection criterion in animal breeding.…”
mentioning
confidence: 99%